The effects of angiotensin I-converting enzyme inhibitory peptide VGINYW and the hydrolysate of α-lactalbumin on blood pressure, oxidative stress and gut microbiota of spontaneously hypertensive rats. Issue 5 (16th February 2022) - Xie, Dewei; Shen, Yaling; Su, Erzheng; Du, Lei; Xie, Jingli; Wei, Dongzhi
Abstract : VGINYW is a highly active angiotensin I-converting enzyme (ACE) inhibitory peptide discovered from α-lactalbumin by an in vitro – in silico high throughput screening strategy. Abstract : VGINYW is a highly active angiotensin I-converting enzyme (ACE) inhibitory peptide discovered from α-lactalbumin by an in vitro – in silico high throughput screening strategy. The aim of this study was to evaluate the antihypertensive effect of the peptide and the α-lactalbumin hydrolysates under 3 kDa (LH-3k), and illustrate the possible mechanism in spontaneously hypertensive rats (SHRs). SHRs were administered with VGINYW and LH-3k at doses of 5 mg per kg BW and 100 mg per kg BW, respectively. VGINYW and LH-3k could markedly decrease the systolic blood pressure (SBP) of the SHRs, and the maximal drops of 21 mmHg (2 h after administration) and 17 mmHg (4 h after administration) were achieved during the 8 hour test, respectively. When the agents were given once per day for 4 weeks, they caused a long-term decrease of 16 mmHg of SBP. VGINYW and LH-3k control the blood pressure through regulating the renin–angiotensin system by inhibiting the ACE activity and diminishing the angiotensin II level, and further upregulating the expression levels of the angiotensin-converting enzyme 2 and angiotensin type 2 receptor, and downregulating the expression of the angiotensin type 1 receptor. VGINYW and LH-3k could notably ameliorate the oxidative stress in the SHR as well. It is more important that the gavage of VGINYW and LH-3k could alleviate hypertension-associated intestinal microbiota dysbiosis by recovering the diversity of the gut microbiota and altering the key floras which are short chain fatty acid producers. In conclusion, VGINYW and LH-3k are effective functional ingredients for blood pressure control.